Growth in situ of NiSe2/Ni hybrids in N-doped carbon nanotubes for enhanced overall water splitting. (20th June 2023) - Wang, Chuanjie; Zhang, Xiao; Zhu, Yuanna; Zhu, Kaili; Luan, Xinxin; Yang, Ping
Abstract: Interface engineering plays an important role to improve the performance of heterostructures. Growth in situ makes the heterostructures with ideal interface natures. Here, the growth in situ of Ni components occurred on N-doping carbon nanotube (Ni-N-CNT) by one-step thermal polymerization for excellent overall water splitting. NiSe2 /Ni-N-CNT with well-developed interface was created by selenium treatment of Ni-N-CNT, which improved the carrier transfer efficiency and increased electrochemical active sites. The formation of NiSe2 /Ni hybrids improved hydrogen evolution reaction (HER). Ni and Se sites were proved in different electrolytes. The overpotential of NiSe2 /Ni-N-CNT at -10 mA·cm −2 was 196 and 220 mV, and Tafel slope is 52 and 70 mV/dec in acidic and alkaline solutions, respectively. NiSe2 /Ni-N-CNT revealed well kinetic effect compared with other control samples both in HER and oxygen evolution reaction (OER). The voltage of the electrolytic cell with NiSe2 /Ni-N-CNT||NiSe2 /Ni-N-CNT electrode was 1.757 and 1.954 V at 10 and 40 mA·cm −2, respectively. NiSe2 /Ni-N-CNT as an electrolytic cell electrode was stable for efficient overall water splitting after 9.5 h. The formation of NiSe2 /Ni-N-CNT heterostructures supplied a utilizable approach for improving HER and OER to get highly efficient catalysts. Graphical abstract: Image, graphical abstract